The Methodology of Libyan Jurists in Issuing Fatwas: الشيخ العلامة محمد مفتاح قريو المصراتي وجوابه في مسألة أجرة العمال والصناع ممن يدفع لهم من القروض المصرفية التي اقترضها بالفائدة الربوية، أنموذجاً - Shaira, Muhammad M. ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2018)
Libyan scholars have long held a distinguished position in the field of Islamic jurisprudence, known for their sharp intellect, deep understanding of texts, and exceptional ability to derive rulings from original sources. A prime example is the fatwa of the late Sheikh Muhammad Muftah Qaryu, who responded promptly and accurately to a legal query, then later provided the same answer in writing, complete with evidences, without altering his original ruling—demonstrating his mastery and memorization. This highlights the importance of reviving and publishing the scholarly works and fatwas of our predecessors. As a relevant example, I present Sheikh Qaryu’s fatwa regarding the permissibility of workers receiving wages paid through interest-based bank loans, a pressing issue in contemporary times due to the widespread use of such loans and frequent public inquiries about their implications in contractual dealings.